Del sujeto de las operaciones al sujeto de la cultura. (2021)
This paper presents a general approach to the different explicative perspectives in cognitive Psychology that have tried to explain the emergency of the psychological conditions of the subject and their relations with the learning and the change. Also it is discussed the pertinence of keep doing reference to formalist models as alternatives to explain the learning and the change and it states proposals through the semiotic-cultural models in psychology as ways to consider the subject inserted in the context and thus co–builder of complex realities in domains of knowledge and experience.